Novel Small-Molecule Inhibitor of NLRP3 Inflammasome Reverses Cognitive Impairment in an Alzheimer's Disease Model - Haseeb, Muhammad; Javaid, Nasir; Yasmeen, Farzana; Jeong, Uisuk; Han, Ji Hye; Yoon, Juhwan; Seo, Jee Yeon; Heo, Jae Kyung; Shin, Ho Chul; Kim, Moon Suk; Kim, Wook; Choi, Sangdun (ACS Chemical Neuroscience, 2022)
Aberrant activation of the Nod-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome plays an essential role in multiple diseases, including Alzheimer's disease (AD) and psoriasis. We report a novel small-molecule inhibitor, NLRP3-inhibitory compound 7 (NIC7), and its derivative, which inhibit NLRP3-mediated activation of caspase 1 along with the secretion of interleukin (IL)-1β, IL-18, and lactate dehydrogenase. We examined the therapeutic potential of NIC7 in a disease model of AD by analyzing its effect on cognitive impairment as well as the expression of dopamine receptors and neuronal markers. NIC7 significantly reversed the associated disease symptoms in the mice model. On the other hand, NIC7 did not reverse the disease symptoms in the imiquimod (IMQ)-induced disease model of psoriasis. This indicates that IMQ-based psoriasis is independent of NLRP3. Overall, NIC7 and its derivative have therapeutic prospects to treat AD or NLRP3-mediated diseases.
Keywords: Alzheimer Disease; Animals; Cognitive Dysfunction; Inflammasomes; Interleukin-1beta; Mice; NLR Family, Pyrin Domain-Containing 3 Protein; Psoriasis; Alzheimer's disease; inflammasome; NLRP3; small-molecule inhibitor; virtual screening